Brand Awareness Communication Strategy in Setujuan Coffee Marketing on Instagram Social Media - Ohorella, Noviawan Rasyid; Fauziah, Dewita; Dalimunthe, Maulana Andinata (Komunika, 2024)
This research aims to find out the marketing communications of Kopi Setujuant in increasing brand awareness and to find out about the marketing promotions of Kopi Secepat on Instagram social media. The method used in this research is a descriptive qualitative approach with a constructivist paradigm. The theory used in this research is the Integrated Marketing Communication theory, this theory is used to see how the marketing promotion strategy is carried out at Kopi Secepat through Instagram social media to attract brand awareness. The data collection techniques used were direct observation, in-depth interviews, documentation and literature study. The results of this research show that coffee marketing communications can increase brand awareness through a design process such as determining the target audience, conducting in-depth research regarding the strategy you want to use, making comparisons with competitors who have the same market, and determining the goals of implementing the strategy with content output.